Enhanced atherosclerosis and kidney dysfunction in eNOS(–/–)Apoe(–/–) mice are ameliorated by enalapril treatment - Knowles, Joshua W. (American Society for Clinical Investigation, 2000)
Hypertension and atherosclerosis are each important causes of morbidity and mortality in the developed world. We have investigated the interaction between these conditions by breeding mice that are atherosclerotic due to lack of apolipoprotein (apo) E with mice that are hypertensive due to lack of endothelial nitric oxide synthase (eNOS). The doubly deficient mice (nnee) have higher blood pressure (BP) and increased atherosclerotic lesion size but no change in plasma lipoprotein profiles compared with normotensive but atherosclerotic (NNee) mice. The nnee mice also develop kidney damage, evidenced by increased plasma creatinine, decreased kidney weight/body weight ratio, and glomerular lipid deposition and calcification. Enalapril treatment abolishes the deleterious effects of eNOS deficiency on BP, atherosclerosis, and kidney dysfunction in nnee mice. In striking contrast, a genetic lack of inducible NOS, which does not affect BP, has no effect on the development of atherosclerotic lesions in Apoe(–/–) mice. We also observed a positive relationship between BP and size of atherosclerotic lesions These results suggest that the atherogenic effects of eNOS deficiency can be partially explained by an increase in BP and reemphasize the importance of controlling hypertension in preventing atherosclerosis.